Stochastic Analysis of a Computer System with Software Redundancy and Failure of Service Facility - S. C. Malik, Amit Kumar, R. K. Yadav (International Journal of Advanced Science and Technology, 2020)
The stochastic analysis of a computer system comprises hardware and software as its two components has been carried out by considering software redundancy in cold standby and failure of service facility.  A single service facility plays a vital role in handling the operational activity of the computer system. The repair of the hardware is done at its failure while software under goes for up gradation in case it fails to do the process as per requirement. The service facility may fail while repairing the hardware and accordingly it under goes for treatment immediately. The repair activities are resumed with full efficiency by the service facility after treatment. The random variables associated with hardware repair time, software up gradation time and treatment time of the service facility follow arbitrary probability distributions. The distributions for failure time of the hardware and service facility are taken as negative exponential. The use of semi-Markov process and regenerative point technique has been taken up for analyzing the reliability measures of the system model at different epochs. The variations in the values of some measures of system effectiveness have been observed for arbitrary values of the parameters.